Participatory ergonomics in Indonesian tin mining - Soejadi, Prijoko P.; Lawson, Glyn; Ryan, Brendan; Hermawati, Setia (Wydawnictwo Politechniki Poznańskiej, 2018)
Thousands of small and medium enterprises’ (SMEs) employees in Indonesian tin mining companies work in dangerous environments without sufficient safety and health protections. This study’s aim was to investigate the identified factors, such as difficulty in communication among stakeholders (owner, manager, and worker), and workers’ negative attitudes towards and lack of knowledge in the use of personal protective equipment that inhibit the implementation of Participatory Ergonomics in Indonesian tin mining companies. Eighteen participants from five SMEs, encompassing three different roles, i.e. worker, owner and manager, participated in the interview study. The study revealed that the dissemination of occupational safety through a kinship approach and specific safety training were preferred to resolve communication, cultural and knowledge problems. The provision of clear definitions of roles and tasks and the allocation of time and resources were suggested as ways to empower workers and supervisors.